Pengorganisasian, Memilih Personil dan Kurikulum Pendidikan dalam Persfektif Hadis Nabi Muhammad SAW - Ramdhan, Dadan; Rosilah, Iis; Khoerulbariyyah, Farah Budiarti; Suarna, Dedi (Melati Institute, 2024)
This research aims to find out the theory of organizing, selecting personnel and educational curriculum in the hadith perspective. This journal uses a qualitative approach with a literature study method. Organization and organizing are two things that are interconnected, if the organization is likened to a container, then organizing is the organism that makes it live. Organizing is the second step in organizational management after planning. Careful planning will not run perfectly, without anyone running and moving, without clarifying the work and who will do it. Therefore it is very important in an organization a personal selection mechanism. Personnel or members of the organization will be very influential in the process of moving the wheels of the organization. In the implementation of the Education Curriculum, it is very necessary to have organizational management and personal / organizational actors who are in line between the character and vision-mission of the organization so that the expected educational goals are achieved. The organization of a good education curriculum results in a good organizational form, starting from the work system, structure, resources to other aspects. This study will discuss organizing, selecting personal and educational curriculum in depth examined from the perspective of the Hadith of the Prophet Muhammad SAW.